(untitled) (University of Khartoum Engineering Journal, 2022)
Variable-rate technology is an essential part of precision farming that can solve the economical andenvironmental problems associated with traditional farming practices. Utilization of the technology has beenlimited by the lack of the development of variable-rate applicators. In this study control system equipped withpneumatic circuit was composed of a double acting cylinder, a double solenoid operated valve 5/2, a computer, amicrocontroller, a rotary encoder, and other operating parts. The control system performance and dischargecharacteristics were evaluated. The main results of this study could be summarized as follows: (i) the automaticsetting of the target fertilizer application rate could be performed efficiently, (ii) the developed system could beprecisely used for granular fertilizer variable rate application, and (iii) the collected observations indicated that thedeveloped system could be significantly used for granular fertilizer variable rate applications with an overall error(from the target rate) in the range of ±6%. This work will be a useful contribution in the area of variable ratetechnology. Further research work to improve the developed control system and to evaluate its performance underactual field conditions is recommended.